Comparison of brushing tooth using a mirror and without mirror to plaque index of orphanage children in Makassar: Perbandingan menyikat gigi menggunakan cermin dan tanpa cermin terhadap indeks plak anak panti asuhan di Makassar - Rachmi Bachtiar; Nur Asmah; Dhyah Selvi Suyono (Makassar Dental Journal PDGI Makassar, 2022)
One of the most common dental and oral diseases in Indonesia today is periodontal disease which is generally caused by plaque bacteria on thetooth surface. To prevent the formation of plaque, maintenance of dental and oral hygiene is carried out in a sim-ple, effective and practicalway, namely by brushing teeth carefully and regularly. Mirroring is one of the media that can reflect oneself clearly because it can see the body including the entire surface of the teeth according to what is reflected in a mirror so that accuracy in brushing teeth is obtained andcleanliness is obtained on all surfaces of the teeth. The purpose of this study was to find how the plaque index compared to brushing teethwith and without mirrors in children at the Ummu Aiman ​​and Hikmah Orphanage in Makassar, using a quasi-experimental method with aposttest only control group design type. Based on the Mann-Whitney U test on 46 samples, a p-value of 0.000 (<0.05) was obtained. This means that there is a significant difference in the dental plaque index in the group that brushes teeth using a mirror and without a mirror. It was concluded that brushing teeth using a mirror was more effective in reducing plaque index than without a mirror.